Extracting buildings in the city of Lisbon using Quickbird images and lidar data - Santos, T. (2011)
The methodology is based on semi-automatic extraction of features, using information from a QuickBird image and LIDAR data. The QuickBird image is suitable to delineate the different elements on the surface based on their spectral characteristics. However, this task is much more successful and richer when altimetric information is also used in the extraction process. Thus, with the introduction of LIDAR data, we intend to study the effect of the contribution of information on the height of urban elements, when classifying orbital data. The thematic information under analysis is the land cover class Buildings. Two maps are produced and compared. One map is obtained by a classification based only on spectral data while the other map is obtained using spectral and altimetric data. The same methodology is applied in both scenarios, using the same training features. To evaluate the quality of the two maps, a comparison with a cartographic layer is carried out. This reference layer is obtained by visual analysis of the QuickBird image and is used to calculate the Overall Accuracy of the maps obtained with the different data sets.